From Hays to Burney: an Approach to Female Difficulties in Early Nineteenth-Century English Fiction - Fernández Rodríguez, Carmen María (Estudios Ingleses de la Universidad Complutense, 2009)
Eighteenth-century female writers depicted patriarchal constraints and produced texts which constitute an interesting reference for the study the representations of gender discrimination. Through an examination of texts and contexts, this work aims at evaluating Frances Burney's contribution to women's fiction in English at the beginning of the nineteenth-century by considering her caricature of the protagonist of Mary Hays's Memoirs of Emma Courtney (1796) in her last novel, The Wanderer or Female Difficulties (1814). Burney portrays an unfeminine woman consumed by unrequited passion, who supports woman's rights and the French Revolution to the extreme. Emma Courtney's intellectual and economic difficulties are affected the hardships endured by Burney's protagonist from the point of view of gender studies. Rather than accomplishing a mere parody, Burney engaged in a powerful critique and offered a realistic vision of woman's position at the turn of the nineteenth century.